PERIODIZATION OF THE PHYSICAL EFFORT – A NEW PRINCIPLE IN KINETOTHERAPY (GYMNASIUM, 2009)
We created an experimental model drawn a specialty literature, to study muscular fatigue. We usedboth research methods surface electromiography and mechanogram.We observed that the shorter muscular contractions and rest intervals are the later muscular fatigueonset in a reasonable time.The duration of muscular contractions and rest intervals influence physical effort intensity.Briefly, I succeeded in creating muscular fatigue quantification by using several physiologicalparameters.